Descrição sensorial de pães isentos de glúten - Tridapalli, Luiza Pelinson (2021)
Gluten is a protein present in cereals like wheat, rye, barley, triticale, and oats, which forms a viscoelastic mass capable of trapping the gas formed during the fermentation and cooking of products. Due to these properties, replacing wheat flour in bread with another ingredient is a challenge. Some people have an intolerance to this protein, which is the case of people diagnosed with celiac disease, whose treatment consists of excluding foods that contain gluten from the diet. Although the space for glutenfree foods has grown in the market, the celiacs report that the supply of appropriate foods that are nutritionally and sensory favored is still restricted. Therefore, the aim of this study was to get a sensory evaluation, through the methodologies of acceptance thesis, Flash Profile, Check-All-That-Apply (CATA), and Just About Right (JAR), of gluten-free bread formulations elaborated with sorghum, teff, and yacon flours. By the experimental design, nine formulations were submitted to the acceptance test, which provided the optimized formulation through the samples' global impression notes. In the following tests, four formulations were used for the samples, being F1 (100% sorghum), F2 (100% teff), F3 (100% yacon), and F4 (optimized formulation, with 33.33% of each flour). F1 was represented by the attributes brown, red and pink colors, bubbles, softness, rind hardness, elasticity, salty, pleasant and bread taste, holes, and bread yeast odor. F2 had a brown color, bubbles, hardness, easy chewing, softness, elasticity, salty taste, and rind texture. F3 was described by the attributes green color, bitterness, sweetness, moisture, ease of chewing, softness, crumb texture, moisture, and sweet taste. F4 was characterized by the attributes green and brown colors, bitterness, sweetness, moisture, easiness of chewing, bubbles, whole-wheat bread odor, tenderness, pleasant flavor, consistency and aroma, and good chewiness, in addition to being the most highly rated in terms of the overall acceptance. These sensory analysis methodologies applied highlighted that some attributes raised by the evaluators may have similar meanings, despite being expressed with different vocabulary, in addition to enabling the obtaining of the descriptive sensory profile of the formulations, evidencing attributes that enable the use of sorghum flour, teff and yacon in the preparation of gluten-free bread and emphasize that the mixture of the three in the optimized formulation had positively impacted the nutritional and sensory characteristics of the product.